Strategy for Innovation and Empowerment by BMT for MSMEs in Wonogiri for 2019-2022 - Rahmadani, Natasya Fika; Apriantoro, Muhamad Subhi (Global Research Network, 2023)
The research objectives include: a) To find out the role of BMT in carrying out innovation and empowerment of Wonogiri SMEs in 2019-2022; b) To find out the constraints of BMT in carrying out innovation and empowerment of Wonogiri SMEs in 2018-2022. The type of research the researcher uses is descriptive-qualitative to understand phenomena regarding the research subject, such as the behavior and ways of words and language researchers in a particular (natural) context using various natural methods. Sources of data used in qualitative research are humans as respondents. Data collection techniques through; a) Interviews/interviews, b) Observations, c) Documentation. In this study, the data analysis technique used by the researcher used the Miles and Huberman model. Data analysis in qualitative research is carried out at the time of data collection and after the completion of data collection within a certain period. The results obtained are BMT Mitra Mandiri in empowerment through training carried out by BMT Mitra Mandiri by collaborating with Human Resources companies. Constraints obtained are intense competition, customers being late in making installments, dishonesty committed by customers where the submissions are not by the implementation in the field, and the marketing process is challenging to motivate MSME actors to carry out innovation strategies so that consumers gain confidence to make purchases.